LANÇADO LIVRO NATURALISM: CONTEMPORARY PERSPECTIVES PELO NEPFIL-UFPEL - Aires de Carvalho, Helder Buenos (Pensando - Revista de Filosofia, 2015)
"It is with great satisfaction that we present the collection of essays Naturalism: Contemporary Perspectives, a work whose aim is to foster the debate on questions relevant to naturalism in the contemporary philosophical scenery. The work originated in the “Research Group on Naturalism, Emotivism, and Normativity” from the Universidade Federal de Pelotas, who since 2012 has been advancing the research and disclosure of contemporary philosophy. This volume brings together some of the main studies proposed in the “I Workshop Understanding Naturalism,” which took place in the same University in April 2013. The aim of this book is to foster high quality philosophical production by Brazilian researchers who have been influenced by naturalist authors and whose approaches may ignite deeper discussions".